An Easy-to-Use Procedure for the Measurement of Total Phenolic Compounds in Olive Fruit - Pilar Luaces; Mar Pascual; Ana G. Pérez; Carlos Sanz (MDPI AG, 2021)
Virgin olive oil (VOO) is one of the most emblematic products of the Mediterranean diet. Its content in phenolic compounds is strongly associated with the antioxidant and health-promoting properties of this diet. VOO's phenolic profile is determined mainly by the phenolic compounds present in the olive fruit, so knowing their content allows for a fairly precise estimate of the antioxidant and functional properties of the corresponding oil. In this sense, a convenient, green, and sensitive spectrophotometric method was developed for the quantitative determination of total phenolic compounds in olive fruits. The method is based on an easy-to-use extraction procedure of olive fruit phenolics using dimethyl sulfoxide and quantification with the Folin-Ciocalteu reagent. Oleuropein proved to be a suitable reference compound for quantification, displaying a good linear response (r = 0.9996) over the concentration range of 0.58-6.48 mg/mL, with a variation coefficient of 0.42% and limits of detection and quantification of 0.0492 and 0.1490 mg/mL, respectively. The method was validated using a wide array of fruit samples representative of the Olea europaea L. genetic diversity. The results obtained with this spectrophotometric method, expressed as mg/mL of oleuropein, showed a good correlation with those obtained with the fruit samples analyzed by high performance liquid chromatography, with an r value of 0.9930 and a slope value of 1.022, confirming its reliability. Thus, this method can become a very useful simple tool to estimate the total phenolic content of olive fruits, especially when working with numerous samples such as in olive breeding programs or in commercial olive production, in which it is especially useful to know the phenolic state of the fruit and thus determine the optimal harvest date or the most appropriate agronomic treatment to increase the functional properties of the olive fruit and the olive oil.